ADDRESSING KNOWLEDGE MANAGEMENT ISSUES AT UNIVERSITY OF HOUSTON: OVERCOMING OBSTACLES TO IMPROVE ORGANIZATIONAL PERFORMANCE - Tariq Tawfeeq Yousif Alabdullah (Transpublika Publisher, 2023)
Effective knowledge management (KM) is crucial for corporate success in today's fast-paced business landscape. This theoretical study explores how KM processes impact organizational performance. It provides a comprehensive framework drawn from existing literature to explain how KM can enhance decision-making, innovation, and operational efficiency when employed strategically. The study highlights key KM components: knowledge creation, dissemination, storage, and application, shaping business success. It categorizes and examines these elements, revealing their intricate relationships. The research explores how an open, collaborative culture promotes knowledge sharing and organizational performance. Additionally, it delves into the role of leadership in fostering a KM-focused culture, emphasizing leaders' influence on knowledge-driven initiatives. It shows how KM practices drive innovation by integrating insights from diverse areas. The study emphasizes leveraging digital platforms for information sharing, despite potential challenges like information hoarding and resistance. Overall, it underscores KM's vital role in organizational performance and provides insights for strategic decision-making in dynamic business environments.